Should There be a Limit to Reproductive Rights? Swan Medal Essay Prize - Byrne, Andrew J. (Trinity Student Medical Journal, 2020)
“Imagine a being who is omniscient, omnipresent and omnipotent. What does such a being lack? The answer? Limitation” (Peterson, 2018). This old Jewish moral teaches an interesting concept: that limitations aren’t flawed or restricting, rather beneficial and necessary. Does that hold true for issues on reproductive rights?